Comparative Study of the Effects of Trabecular Meshwork Outflow Drugs on the Permeability and Nitric Oxide Production in Trabecular Meshwork Cells - Kim, Jae Woo (Korean J Ophthalmol, 2017)
PURPOSE: To compare the effects of the barrier function in human trabecular meshwork (TM) cells monolayer and the production of nitric oxide (NO) between trabecular outflow drugs, Rho-associated kinase (ROCK) inhibitors, adenosine, and statin. METHODS: Primary cultured TM cells were exposed to 10 or 25 µM Y-27632, 0.1 or 1 µM N6-cyclohexyladenosine (CHA), or 15 or 30 µM simvastatin for 24 hours. NO production and expression of endothelial nitric oxide synthase mRNA were measured by Griess assay and reverse transcription polymerase chain reaction, respectively. Barrier functions of the TM cell monolayer were measured by carboxyfluorescein and trans-endothelial electrical resistance. The expression of matrix metalloproteinase-2 mRNA was assessed with reverse transcription polymerase chain reaction. RESULTS: In TM cells, treatment with each drug increased endothelial nitric oxide synthase mRNA expression. Treatment with 25 µM Y-27632 and 1.0 µM CHA increased NO production significantly (p = 0.035 and p = 0.043, respectively). Treatment with each drug increased the permeability (all p = 0.001) and decreased the trans-endothelial electron resistance of the TM cell monolayer. Treatment with 0.1 µM and 1.0 µM CHA significantly increased matrix metalloproteinase-2 mRNA expression, but simvastatin inhibited its expression. CONCLUSIONS: Since treatment with ROCK inhibitor more greatly increased NO production and permeability than did adenosine or statin, ROCK inhibitor seems to be more effective for lowering intraocular pressure.